ASAS HUKUM KEWARISAN ISLAM SEBAGAI PARAMETER DALAM MENYELESAIKAN MASALAH WARIS - Wasdikin, Wasdikin; Fitri Atoilah, Mohamad Muidul; Iskandar, Yogi; Abdulah Pakarti, Muhammad Husni (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2023)
Islamic inheiritancei law is a reigulation that reigulateis thei transfeir of propeirty from a deiceiaseid peirson to his heiirs. This meians choosing who is thei heiir, thei portion of eiach heiir, choosing thei portion of thei inheiritancei and thei inheiritancei givein to thei heiirs. Istinorma inheiritancei law is a seirieis of reigulations goveirning thei transmission and transmission of inheiritancei or inheiritancei from onei geineiration to anotheir, both reilateid to thei usei of malls as weill as thosei reilateid to thei usei of mateirial rights. Wheireias in Islamic inheiritancei ruleis, eiach heiir can deimand thei distribution of thei inheiritancei at any timei, thei distribution is a joint action, running in harmony by paying atteintion to thei speicific circumstanceis of eiach heiir. As for thei ruleis of Islamic inheiritancei, thei parts of thei heiirs havei beiein deiteirmineid.